Fashion Reset: Ctrl + Alt + Del: a communication campaign aimed at raising awareness, improving sentiment and driving adoption of sustainable fashion among Nanyang Technological University students - Chan, Anna Kai An (Nanyang Technological University, 2023)
This paper presents Fashion Reset: Ctrl + Alt + Del, a communication campaign aimed at raising awareness, improving sentiment and driving adoption of sustainable fashion (SF) habits among female Nanyang Technological University (NTU) students aged 19 to 25. Despite the trending topic of SF, the lack of action taken to alleviate issues on sustainability despite prior intentions to do so, has been a problem identified among members of Gen Z globally. This lack of action will continue to harm the environment unless we bridge this gap and inspire adoption of SF habits. Our campaign focused on promoting six SF options that lengthen the lifespan of the products and minimise fashion and textile waste. These options include buying second-hand clothes, thrift shopping, mending or repairing clothes, repurposing or upcycling clothes, clothes swapping and clothes rental. In three months, we managed to meet our objectives in increasing awareness of and engagement with these SF options. However, we were less successful in meeting our attitudinal objectives of increasing the percentage of our target audience (TA) who have confidence in and have intention to engage in SF options, which we will discuss in this paper. We developed a pilot campaign introducing an experiential take on SF options through multiple physical events on campus. In addition, we used Instagram (IG) and TikTok to educate our TA on SF, and to promote our campaign online. This paper will cover the formative research, objectives, and strategy development, as well as campaign tactics, implementation, post-campaign research and the campaign’s impact.